Bayesian cognitive modeling : a practical course - Lee, Michael D. (Michael David), 1971-; Wagenmakers, Eric-Jan (Cambridge : Cambridge University Press, 2013)
Bayesian inference has become a standard method of analysis in many fields of science. Students and researchers in experimental psychology and cognitive science, however, have failed to take full advantage of the new and exciting possibilities that the Bayesian approach affords. Ideal for teaching and self study, this book demonstrates how to do Bayesian modeling. Short, to-the-point chapters offer examples, exercises, and computer code (using WinBUGS or JAGS, and supported by Matlab and R), with additional support available online. No advance knowledge of statistics is required and, from the very start, readers are encouraged to apply and adjust Bayesian analyses by themselves. The book contains a series of chapters on parameter estimation and model selection, followed by detailed case studies from cognitive science. After working through this book, readers should be able to build their own Bayesian models, apply the models to their own data, and draw their own conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cognitive science -- Mathematical models; Bayesian statistical decision theory